Microseismicity Monitoring and Site Characterization With Distributed Acoustic Sensing (DAS): The Case of the Irpinia Fault System (Southern Italy). Issue 9 (24th September 2022) - Trabattoni, A.; Festa, G.; Longo, R.; Bernard, P.; Plantier, G.; Zollo, A.; Strollo, A.
Abstract: This paper reports the first results obtained thanks to the installation of a dedicated one‐km fiber‐optic cable, integrated within the Irpinia Near Fault Observatory regional network in Southern Italy. The cable was installed in a dry lake, located near the active faults responsible for the M6.9 earthquake that occurred in 1980. A distributed acoustic sensing (DAS) interrogator was deployed over a period of 4 months and a half and allowed to record tens of local events. To model the seismic phases observed in the recordings, simple seismic refraction experiments were conducted along with analyses of earthquakes and numerical simulations. Results show that in this peculiar geological context, DAS is mainly sensitive to waves guided horizontally by the subsurface low‐velocity layered structure of the site. This leads to considerable site amplification but also wavefront deformation and allows to detect local microearthquakes without any stacking or other array processing techniques. Magnitude estimation was performed using a dedicated amplitude correction process, along with detection threshold estimation. The benefit of using stacking of DAS channels for improving signal‐to‐noise ratio was also estimated. Plain Language Summary: A fiber‐optic cable was buried near the fault responsible for the devastating earthquake that struck the Irpinia region (Southern Italy) in 1980. A specialized instrument, called distributed acoustic sensing (DAS) interrogator, was used to measure micrometric deformations of the cable due to small earthquakes regularly produced by the faults. The ground where the cable was installed is composed by stratified and very soft materials which trap and amplify seismic waves. Through analysis and modeling, we demonstrated that DAS is particularly sensitive to those effects because of its measuring principle. We showed that wave amplification allows to record small earthquakes otherwise impossible to detect and that their magnitude can be estimated if corrections are applied. We characterized the wave deformation process, a first important step to enable the use of conventional detection and location techniques and unleash the true potential of DAS deployments in geological context presenting soft materials. Key Points: An active tectonic area was monitored by a new dedicated fiber‐optic cable deployed in a dry lake near a major fault Recordings were dominated by highly amplified waves with slow apparent velocities Modeling suggests that distributed acoustic sensing is particularly sensitive to site effects whereas energy analysis enables magnitude estimation